Pemberdayaan Perekonomian Masyarakat Desa Jubung Melalui Pemberdayaan Usaha Mikro Kecil dan Menengah (UMKM) - Kartika Putri, Della Aprilia Kartika Putri; Fatiya Diana Wulandari Putri; Rahayu Rahmawati (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
This research aims to analyze efforts to empower the economy of village communities through improving and developing Micro, Small and Medium Enterprises (MSMEs) using Anthony Giddens' Structuration theory. The research method used is a qualitative approach. The method for determining the research location uses the purposive area method, namely in Jubung Village, Sukorambi District, Jember Regency. Determining research informants used the purposive sampling method. The informants in this research were MSME actors and the village government in Jubung Village. Data collection includes observation, interviews, and documentation, then the data analysis process includes data collection, data reduction, data display, and conclusion drawing. The research results show that the village government in empowering MSMEs in Jubung Village has carried out its role well by providing a special platform or place for MSME actors to enable them to produce and market their goods. Apart from that, the Jubung Village government is trying to propose and seek budget support and technical assistance from related agencies, such as the Cooperatives Service.